Why Cooperative Societies are Collapsing in Nepal - Bist, Kapil; Dahal, Gangadhar (Nepalese Journal of Management, 2025)
This study examines the why are cooperative societies are collapsing in Nepal. Collapse of cooperative societies is the dependent variable. The selected independent variables are regulatory environment, financial management practices, Market competition, social capital, Government support. The primary source of data is used to assess the opinions of respondents regarding regulatory environment, financial management practices, Market competition, social capital, Government support, Collapse of Cooperative Societies. The study is based on primary data of 110 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of why are cooperative societies collapsing in Nepal The study shows that regulatory environment is negatively correlated to the collapse of cooperative Societies. It indicates that in regulatory environment decrease likelihood collapse of cooperative societies. Likewise, f inancial management practices is negatively correlated to the collapse of cooperative societies. It indicates that increase in better financial management Practices leads to decrease in collapse of cooperative societies. Furthermore, market competition is negatively correlated to the collapse of cooperative societies. It indicates that increase in market competition leads to decrease in collapse of cooperative societies. Likewise, social capital is negatively correlated to the collapse of cooperative societies. This implies that improvement in social capital leads to the decrease in collapse of cooperative societies. Similarly, government support is negatively correlated to the collapse of cooperative societies. It indicates that in government support leads to the decrease in collapse of cooperative societies.